EFFECTS OF ORGANIC FERTILIZER TYPES AND DOSAGE ON BIOLOGICAL PROPERTIES OF SOIL, GROWTH AND PRODUCTS OF ONION (Allium ascalonicum L.) OUTSIDE THE PLANTING SEASON IN BUAHAN VILLAGE, BALI, INDONESIA - Kartini, Ni Luh (International Journal of Biosciences and Biotechnology; Vol 8 No 2 (2021): International Journal of Bioscience and BiotechnologyDO - 10.24843/IJBB.2021.v08.i02.p02, 2021)
Planting shallots in Buahan Village is only carried out once a year, namely in July. The continuous use of synthetic fertilizers at high doses without being balanced with natural fertilizers has degraded the land so that soil fertility has decreased. The negative impact caused is a decrease in the yield of shallots. Quality organic fertilizers can overcome this problem. Organic vermicompost and biosllury fertilizers are quality organic fertilizers that can replace synthetic fertilizers to increase the growth and yield of shallots. The research objective was to determine the growth and yield of shallots by giving the type and dose of organic fertilizers outside the growing season. The research was conducted from March to July 2019 in Buahan Village, Kintamani District, Bangli Regency. The study used a simple randomized block design with one factor with 6 treatments, namely B 0 (Without Organic Fertilizer), B 1 (2000 kg / ha vermicompost); B 2 (1000 L / ha biosllury) B 3 (1000kg / ha vermicompost + 500 L / ha biosllury); B 4 (4000 kg / ha vermicompost); B 5 (2000 L / ha biosllry); B 6 (2000kg / ha vermicompost + 1000 L / ha biosllury); B 7 (4000 kg / ha vermicompost + 2000L biosllry) and B 8 (5000 kg / ha vermicompost + 3000L / ha biosllury). The parameters observed were plant height, number of tillers, tuber wet weight per clump, harvest dry weight of tubers per clump and number of cloves per clump, soil pH, N-total (%), C-organic and total population of soil microorganisms. The results showed that the type and dose of organic fertilizer had a significant effect on all the meters observed. Treatment of 5000 kg / ha vermicompost + 3000L / ha biosllury gave the highest yield, namely 56.8 g per clump, 60% higher than the control 35.5 g per clump.